2017
DOI: 10.1155/2017/3161680
|View full text |Cite
|
Sign up to set email alerts
|

25-Gauge Vitrectomy in Open Eye Injury with Retained Foreign Body

Abstract: Purpose. Ocular trauma with retained foreign body is an important cause of visual impairment in working-age population. Clinical status impacts on the timing and planning of surgery. In the last year small gauge vitrectomy has become safer and more efficient, extending the range of pathologies successfully treated. Aims. To evaluate the safety and outcomes in patients with open eye injury with retained foreign body that underwent early 25-gauge vitrectomy. Methods. In this retrospective, noncomparative, interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although PPV brought novelty and safety to IOFB extrapolation, nowadays there is no consensus on a standard technique (28). Sborgia et al have shown that sutureless 25-gauge pars plana vitrectomy may be useful in the removal of IOFBs because it is associated with a less traumatic appearance, less conjunctival damage, less intraocular inflammation, and faster healing of sclerotomies compared with 20-gauge PPV (34). To our knowledge, there is no data comparing the 25-gauge to the 23-gauge system.…”
Section: Discussionmentioning
confidence: 99%
“…Although PPV brought novelty and safety to IOFB extrapolation, nowadays there is no consensus on a standard technique (28). Sborgia et al have shown that sutureless 25-gauge pars plana vitrectomy may be useful in the removal of IOFBs because it is associated with a less traumatic appearance, less conjunctival damage, less intraocular inflammation, and faster healing of sclerotomies compared with 20-gauge PPV (34). To our knowledge, there is no data comparing the 25-gauge to the 23-gauge system.…”
Section: Discussionmentioning
confidence: 99%
“…23,[65][66][67] Patients with traumatic endophthalmitis should be administered intravitreal antibiotics during surgery. [68][69][70][71][72] However, approximately 4% of patients still end up with eyeball atrophy, mostly caused by ciliary body damage induced by severe mechanical ocular trauma, recurrence of RD, or incomplete treatment of endophthalmitis. [73][74][75][76]…”
Section: Recommendation Explanationsmentioning
confidence: 99%
“…In the past decades, pars plana vitrectomy(PPV) has been advocated and widely used in removing IOFB [ 6 , 7 ]. Comparing with external electromagnet, PPV provides a direct visualization and allows a timely management of vitreous hemorrhage and retinal detachment, which would result in better anatomic outcomes, visual prognosis and reduce the risk of endophthalmitis development [ 8 ].…”
Section: Introductionmentioning
confidence: 99%